2016
DOI: 10.1111/den.12704
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasonography‐guided transmural drainage of walled‐off pancreatic necrosis: Comparison between a specially designed fully covered bi‐flanged metal stent and multiple plastic stents

Abstract: BFMS appear to be superior to MPS for EUS-guided WON drainage in terms of clinical success, number of DEN sessions, adverse events, need for salvage surgery and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 19 publications
3
97
0
1
Order By: Relevance
“…However, 75% (3/4) bleeding cases in LAMS of our study was observed at about 1 week after procedure, indicating that early bleeding might be more frequent than expected. To confirm this finding, studies reporting the time and outcomes of bleeding were systemically retrieved in Table S1 and summarized in Table . Generally, bleeding was reported in 34 patients from eight studies during the first 3 weeks, which was reported in only 16 patients from six studies 3 weeks after intervention.…”
Section: Discussionmentioning
confidence: 90%
“…However, 75% (3/4) bleeding cases in LAMS of our study was observed at about 1 week after procedure, indicating that early bleeding might be more frequent than expected. To confirm this finding, studies reporting the time and outcomes of bleeding were systemically retrieved in Table S1 and summarized in Table . Generally, bleeding was reported in 34 patients from eight studies during the first 3 weeks, which was reported in only 16 patients from six studies 3 weeks after intervention.…”
Section: Discussionmentioning
confidence: 90%
“…In recent studies comparing plastic with metal stents - the AEs were either similar or lower in the metal stent group (Table 2)[52-55,76]. Metal stents can tamponade the edges of cysto-gastrostomy site, thereby reducing the occurrence of bleeding from puncture site.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Since the publication of this systematic review, multiple studies have demonstrated improved outcomes for the treatment of WON when using metal stents, with fewer endoscopic necrosectomy sessions required to achieve resolution, fewer adverse events, shorter hospital stay and reduced need for salvage surgery [27,31]. Furthermore, a recent study found superior resolution rates of WON at 6 months follow-up when drainage had been performed with metal stents (both straight FcSEMS and LAMS) than with PS [27].…”
Section: Metal Vs Plastic Stentsmentioning
confidence: 99%